2014
DOI: 10.1063/1.4895229
|View full text |Cite
|
Sign up to set email alerts
|

Green polymer electrolytes based on chitosan and 1-butyl-3-methylimidazolium acetate

Abstract: Structure and ionic conductivity of ionic liquid embedded PEO-LiCF 3 SO 3 polymer electrolyte AIP Advances 4, 087112 (2014)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In the present study, the diffractogram of the pure chitosan sample exhibits a characteristic peak at 2θ = 21.0°, confirming the ordered structure. In other words, CS exists in a relatively high degree of crystallinity [ 36 ]. Figure 3 a exhibits several numbers of crystalline peaks for the parent CS, which possesses two deep peaks centered at 2θ° = 15° and 20°, emphasizing the existence of a crystalline part in the parent chitosan membrane with an average intermolecular distance [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the diffractogram of the pure chitosan sample exhibits a characteristic peak at 2θ = 21.0°, confirming the ordered structure. In other words, CS exists in a relatively high degree of crystallinity [ 36 ]. Figure 3 a exhibits several numbers of crystalline peaks for the parent CS, which possesses two deep peaks centered at 2θ° = 15° and 20°, emphasizing the existence of a crystalline part in the parent chitosan membrane with an average intermolecular distance [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 4 b, there are two other peaks that appear at 1651 and 1554 cm − 1 which correspond to carboxamide (O=C–NHR) and amine (NH 2 ) bands, respectively [ 54 ]. The peak at 1550 cm − 1 is associated to N–H bending of a primary amide (−NH 2 ) [ 36 ]. It is interesting to note that as the quantity of NH 4 I salt is increased, a number of peaks become broader their intensities are reduced as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leones et al [234] stated that ionic liquids are preferred over common inorganic salts and are compatible for mixing with most polymer matrices, thereby allowing the development of composite membranes with smooth structure and good flexibility. This statement was proven true in the study conducted by Shamsudin et al [235,236], which involved a mixture of chitosan matrix with 1-butyl-3-methylimidazolium acetate [Bmim] [OAc]. From SEM micrographs (Figure 18), it was observed that with increasing addition of [Bmim][OAc], the surface morphology was transformed and became smoother with smaller pores, thereby indicating the reduction of crystalline phase and enhancement of amorphous region in the polymer matrix.…”
Section: Cs-ionic Liquid Composite Membranementioning
confidence: 67%